Environmentally Friendly, Semi-transparent, Screen Printed Antenna for RFID Tag Applications - Marques, Alisson Henrique Ferreira; dos Santos, Danilo [UNESP]; de Oliveira Vieira, Kayo [UNESP]; Quadros, Matheus Henrique; Rebello, Pedro Henrique Pereira; Ferro, Vinícius Lourenço Dias; dos Santos, Elson; Fellegara, Henry; Valério, Paula; Fugikawa-Santos, Lucas [UNESP]; Gomes, Tiago Carneiro [UNESP]; Gozzi, Giovani [UNESP] (Springer Nature, 2021)
Wireless communication employing radio-frequency identification (RFID) tags is progressively more widespread in a variety of industrial and commercial sectors. Aspects as demanding specific needs regarding reading distance, production cost, and processability are requested for commercial applications. Nowadays, printing of optical barcodes is the most economically technology for short distance (up to ~30 cm) reading applications. However, the large-scale and low-cost printing of RFID tags would be a competitive alternative to barcode technology because it allows quicker identification with much less reading errors. Here we demonstrate a semi-transparent, screen printed RFID antennas using a non-metallic and environmentally friendly conductive paste. The variation of the film thickness (from 2.5 up to 15 µm) permitted the fabrication of antennas with reading range (0.84–3.29 m), sheet resistance (6.2–36 Ω/sq), and optical transmittance (0–32.3%), which are compatible to commercial or industrial applications aiming short to moderate reading distances.
Keywords: Conductive ink; Environmentally friendly; Printed electronics; RFID Antenna; Transparent ink; Wireless